Impact of Decrease in Cultural Tourism Visits on Gross Regional Domestic Product of Blitar Regency During The Covid-19 Pandemic - Siti Arifah; Ilmiawan Auwalin; Alissa Qodrunnada; Rezhi Vauzi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
The COVID-19 virus has become a global pandemic and has spread to various countries, including Indonesia. The pandemic causes turmoil in the health sector and the economy. The impacts of the pandemic are not only at the national level but also the provincial and district level. The district of Blitar is no exception. Blitar is a district in East Java Province with a diverse cultural heritage. Cultural tourism directly contributes to the regional revenue, which can help the recovery of the local economy. This study examines the impact of the COVID-19 pandemic on the number of cultural tourism visits and its implications on the Gross Regional Domestic Product (GRDP) of Blitar. The results show that while the tourist visits contribute to the GRDP of Blitar, the contribution has been negatively impacted by the pandemic.